Isolation and Identification of Egg Drop Syndrome Virus with Hemagglutination and Hemagglutination Tests - Fidyah Fitrawati; Michael Haryadi Wibowo; Surya Amanu; Bambang Sutrisno (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2015)
Egg drop syndrome (EDS) is a disease that attacks layer hens in the production phase causing failure of peak eggs production, decreased in eggs production, and presence of eggs without shell. This study was conducted to isolate and identify the EDS virus in the chicken layer that was diagnosed as a disease of EDS by hemagglutination (HA) and hemagglutination inhibition (HI) assays. Specific pathogen free (SPF) layerchickens which were passing through the production phase fed with food which was mixed with egg without shell from SR/WNO/2011. The chicken together with chicken FF/Sleman/2011 were dissected when pathological lesions, such as the dents or palor eggs observed. The uterine tissues were then collected for samples. Infundibulum of chicken FF/Sleman/2011 was explored and was found out that the eggs were lack ofegg shells. The eggs were then washed using sterile PBS. The three subsequent samples were propagated in the allantoic fluid of embryonated duck eggs for 16 days. Allantoic fluid was harvested after being incubated for 4 days. It was then tested by HA and HI assay by use of avian influenza virus (AIV), Newcastle disease virus (NDV), and EDS anti serum. The HA and HI test with EDS anti serum used chickens erythrocytes in percentageof 0,8. The HA test in uterine sample of both SR/WNO/2011 and FF/Sleman/2011 showed the titer 23 HA units and egg washed water sample of FF/Sleman/2011 showed titer 22 HA units. The HI test for comparison with ND and AI anti serum was negative, while the test with EDS anti serum showed positive results. Based on the HA and HI test results, it was concluded that the virus grown in the allantoic fluid is EDS virus.